Enhanced high-spatial resolution radiographic images based on COTS CMOS image sensors applied to wood dendrochronology and densitometry - Corzi, Damián Leonel (2024)
The imaging of wood samples using X-rays for the study of dendrochronology and densitometry is predominantly conducted through analog films subsequently digitized or, in more advanced instances, with expensive flat-panel systems characterized by resolutions on the order of tenths of microns. For this reason, this work proposes as an alternative the utilization of Commercial-Off-The-Shelf (COTS) complementary metal–oxide– semiconductor (CMOS) image sensors as affordable direct detectors for the acquisition of 10.2 μm resolution radiographic images, which represents sufficient resolution to observe the small structures formed by wood cells called tracheids. The raw images are subsequently processed to mitigate the impact of non-uniformities inherent in pixel response, including the total dose effects, and artifacts present in the image generated by irregularities and defects in the materials utilized to support the wood samples. Moreover, an exhaustive study of the sensor response over different x-ray tube voltage was performed, comparing the results obtained with a simple calculation model and finding a negligible contribution of the photons above the 20 keV. The model was developed based on diverse analyses of geometry and composition of the sensor, such as Focus Ion Beam, Scanning Electron Microscopy, and Time-of-Flight Secondary Ion Mass Spectrometry, and takes into account the X-ray beam attenuations and the photon interaction with the sensor. Finally, this model enables the estimation of the transmission based on the density and thickness of the wood samples.